INTEGRATION OF THE SPECIAL ECONOMIC ZONES IN THE LOCAL ECONOMY:THE CASE OF SPECIAL ECONOMIC ZONES IN CAVITEPROVINCE - Rocela, Michele M. (PEOPLE: International Journal of Social Sciences, 2015)
The main objective of this study was to examine and analyze the status of integration of the Cavite Special Economic Zones in the local economy. In order to determine the status of integration of the Cavite Special Economic Zones, it is important to note if these SEZs were able to generate employment opportunities to the locals. Moreover, the different types of local businesses that emerged in the area after the establishment of the special economic zones in the different municipalities in Cavite where these SEZs are located were also considered. Likewise an in-depth analysis of the role of the local government in local economic development was also considered since the local government unit plays an important role in achieving the goal of this export-led strategy, establishing SEZs in the area. Lastly, the factors considered by the Locators when they decided to establish their businesses inside the SEZs in the province of Cavite were also included in the analysis.The researcher used the descriptive method and a multi-stage sampling. The researcher had to select a sample which can represent the pulse of the entire population of the SEZ Locators. The researcher used the survey questionnaire. Aside from the survey questionnaire, the researcher also used the interview method wherein a combination of formal and informal styles or the semi-standardized formats were used. Lastly, the researcher also used the focus group discussion and actual observation of the area as tools in gathering data. Thirty-five (35) locators or (6.61%) of the total number of locators out of the five hundred thirty (530) locators declined to give information/details about their businesses due to confidential reasons. Therefore, there were four hundred ninety-five (495) or (93.39%) locators subjected to interviews and survey. Results showed that the Special Economic Zones in the province of Cavite are highly integrated with the local economy.